The incidence of prostate cancer and urothelial cancer in the prostate in cystoprostatectomy specimens in a tertiary care Canadian centre - Sivalingam, Sri (Canadian Medical Association, 2013)
INTRODUCTION: Radical cystoprostatectomy remains the gold standard treatment for muscle invasive bladder cancer. However, given the treatment related complications of compromised potency and continence with this procedure, prostate/sexuality sparing cystectomy in orthotopic neobladder candidates has emerged in an effort to minimize these quality of life concerns. Recent evidence suggests only a marginal functional benefit from these technical refinements. We sought to determine the incidence of occult prostate cancer and urothelial cancer of the prostate in cystoprostatectomy specimens conducted for muscle invasive bladder cancer. METHODS: We retrospectively reviewed 83 male patients who underwent radical cystoprostatectomy for muscle invasive bladder cancer between April 2004 and March 2007. The median age of our study group was 71 years. Pathologic findings of prostate/urothelial cancer in the prostate were identified. Clinically significant prostate cancer was defined as Gleason score >6, tumour volume >0.5cc, extracapsular extension or perineural invasion. RESULTS: Our review yielded a 30% (±10%, 0.95 CI) rate of prostate cancer, with 19% (± 8.5%, 0.95 CI) of total specimens being positive for clinically significant prostate cancer. Urothelial cancer in the prostate was identified in 16% (±8.5%, 0.95 CI) of patients, with an overlap with prostate cancer in 2 patients. The overall rate of an underlying cancer within the prostate of our cystoprostatectomy specimens was about 46% (±10.7%, 0.95 CI). CONCLUSION: These findings suggest that the oncological risk of leaving behind residual cancer may not justify the practice of prostate-sparing cystectomies.